Assessment of Marine Protected Areas in Four Coastal Barangays of Bolinao, Pangasinan - Paz-Alberto, Annie Melinda; Teñoso, Annie Rose D. (Silliman Journal, 2022)
This study aimed to assess the diversity of fish and macrophytes present in the marine protected areas (MPAs) in Barangays Balingasay, Arnedo, Victory and Binabalian in Bolinao, Pangasinan, and to determine the physical, chemical and biological characteristics in order to evaluate the present condition in these marine protected areas. The physical and chemical characteristics of the selected coastal areas in Bolinao were found to be of good water quality being within the optimum level set by DENR for marine species to thrive and replenish. The total coliform was high due to the presence of milkfish pens nearby and domestic wastes from residential areas. Twenty marine fish species were identified from the four marine protected areas: 14 were found in Arnedo, 16 in Balingasay, 5 in Binabalian, and 5 in Victory. Overall four species, namely Chromis dimidiata, Acanthurus olivaceus, Halichoeres hortulanus, and Chlororus microrhinos registered a high importance value index. The diversity of the marine fish species in the said areas was very low. Only 9 macrophytes were identified—7 seagrasses and 2 seaweeds. Eight macrophytes were found in Barangay Arnedo, 5 in Balingasay, 4 in Binabalian, and 5 in Victory. Thalassia hemprichii and Caulerpa racemosa had the highest percent cover in almost all of the study areas for macrophytes. The marine protected areas in Bolinao, Pangasinan have low diversity of fish and macrophytes and high total coliform due to anthropogenic activities. The marine protected areas have only recently made a modest start on their way towards the rehabilitation of the coastal resources. Hence, a no take zone is imperative to bring back the integrity of the coastal resources. This would constitute a step towards the attainment of sustainability.